2019
DOI: 10.1007/s40477-019-00383-4
|View full text |Cite
|
Sign up to set email alerts
|

Point of care ultrasound (POCUS) in Canadian neonatal intensive care units (NICUs): where are we?

Abstract: Objectives Despite increased evidence that point-of-care ultrasound (POCUS) has the potential to improve patient care in many clinical areas, the extent of use and training in POCUS in Canadian neonatal intensive care units (NICUs) has not been described in the literature. In this study, we aimed to explore the extent to which POCUS is being used and the need for a formal curriculum with defined POCUS competencies in the field of Neonatal-Perinatal Medicine (NPM). Methods We sent a cross-sectional electronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…[30][31][32] Furthermore, more NICUs worldwide appear to be adopting non-invasive diagnostic modalities such as of point-of-care ultrasound for line placement, effusion checks, and assessment of necrotizing enterocolitis. [33][34][35][36][37][38][39][40][41][42][43] This study highlights the various changes in different procedures being performed in the NICUs in the United States. Our findings regarding the decreased utilization of exchange transfusion as a therapeutic modality in the management of hyperbilirubinemia is in line with reports from Canada, California, Jordan, and India with advent of universal screening guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Furthermore, more NICUs worldwide appear to be adopting non-invasive diagnostic modalities such as of point-of-care ultrasound for line placement, effusion checks, and assessment of necrotizing enterocolitis. [33][34][35][36][37][38][39][40][41][42][43] This study highlights the various changes in different procedures being performed in the NICUs in the United States. Our findings regarding the decreased utilization of exchange transfusion as a therapeutic modality in the management of hyperbilirubinemia is in line with reports from Canada, California, Jordan, and India with advent of universal screening guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…adopting non-invasive diagnostic modalities such as of point-of-care ultrasound for line placement, effusion checks, and assessment of necrotizing enterocolitis 33,34,43,[35][36][37][38][39][40][41][42] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The P2Network is developing tools to define and evaluate competency in PEM POCUS applications for PEM providers. Assessing competency in POCUS education and training, in general, is an active area of research 47–57 . For example, ACEP has recommended that learners complete a predefined number of POCUS studies to be considered proficient.…”
Section: The Approach Of P2network To Address Pem Pocus Educational N...mentioning
confidence: 99%
“…A recent survey done by the author, Ben Fadel N et al (2019), indicated that NPM trainees unanimously agree that the learning of ultrasound skills offers many benefits when it comes to patient care, and acquiring them is very important for their future careers. However, there is a lack of formal curriculum for both hands-on ultrasound skills and image interpretation skills, both of which are urgently needed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%